Developing a Model for Selection of Employee Training Approaches in Small and Medium Industrial Enterprises in Ahvaz - hadith Jalilian; yadollah mehralizadeh; gholamhossain Rahimidoust (Shahid Chamran University of Ahvaz, 2021)
The purpose of this study was to develop a model for selecting employees' educational approaches in small and medium industrial companies in Ahvaz. This study reached theoretical saturation using qualitative approach and foundation data theory method after interviewing 11 managers and employees of small and medium industrial companies of Ahvaz number one. After analyzing the results of eight oral questions during free coding, axial coding and selective coding, the overall pattern of the research was finally extracted. Paradigm Research Model in Causal Conditions (Including Individual Factors: Adaptation to Corporate Needs and Employee Behavioral Factors and Organizational Factors: Managers' Performance Related to Educational Facilities, Economic Problems and Laws), Contextual Conditions (Management and Policies) And staff responses), intervening conditions (social and economic factors), strategies (enhancing people's skills and experiences and empowerment, updating facilities, formulating appropriate laws and regulations, and training individuals (formal, informal and free courses)), The Central Phenomenon of the Paradigm Model that Includes Human Resource Development and Outcomes (Individual Level: Human Resources Training The expert, developing talents and motivate people and organizational level: to optimize production and enhance the reputation and credibility of the organization) was designed. Considering the main purpose of the study, which was to formulate the model of selection of staff training approaches (supportive, non-supportive, neutral and contingent) and to consider teaching-learning approaches that include formal, informal, and free training, it was finally found that most Managers choose a contingency approach and at the end the general model of the research is extracted.MethodThe method in this research is Grounded Theory. Grounded Theory is that discovers theories, concepts, hypotheses, and theorems directly from data, rather than inferring from previous assumptions, other existing research, or theoretical frameworks.ResultsFinally, according to the main purpose of the study, which is to develop a model for selecting staff training approaches (supportive, non-supportive, neutral and contingent) and considering teaching-learning approaches that include formal, informal and free training, it was found that most managers choose a contingency approach and finally the general research model is extracted.DiscussionIn the last decade, with the advent of new technologies in production, communication, change in the capabilities of industrial units, production methods, distribution and organizational structure of enterprises has emerged, which has mainly increased the importance of small and medium units. Humanity has a significant role. In this research, unlike previous research, it has been implemented in the conditions of inflation and economic recession.